A review: fibres, polymer matrices and composites - Norizan, Mohd Nurazzi; Abdan, Khalina; Salit, Mohd Sapuan; Abang Abdul Majid, Dayang Laila; Mohamed, Rahmah; Zin, Mohd Hanafee (Universiti Putra Malaysia Press, 2017)
The growing interest, environmental consciousness and high performance demands on engineering have led to extensive research and development of new and improved materials. Among the most commonly used natural fibres are kenaf, oil palm, sugar palm, pineapple leaf fibre, flax, hemp, sisal, coir and jute. These fibres are used to reinforce thermoplastic polymer matrices such as polystyrene (PS), polypropylene (PP), polyethylene (PE) and polyvinyl chloride (PVC). Meanwhile, phenolic, unsaturated polyester vinyl ester and epoxy resin are for thermosetting polymer matrices. The objective of this paper is to solicit works that cover major class of natural fibres, thermosetting polymers matrices, which detail about unsaturated polyester resin and hybrid biocomposites industry.